(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: The establishment of Cardiac Surgery at Chittagong Medical College Hospital (CMCH) in 2012 marked a significant milestone for Coronary Artery Bypass Grafting (CABG) in the region. CABG requires a skilled multidisciplinary team, including surgeons, anesthetists, perfusionists, operating theater and ICU staffs. This study evaluates the outcomes of CABG procedures at CMCH, addressing the challenges of starting such services in an underserved area. Methods: A retrospective analysis was performed on 201 patients who underwent CABG at CMCH between April 2013 and December 2023. Data on patient demographics, surgical techniques, perioperative complications and postoperative outcomes were analyzed to assess mortality and morbidity. Results: The outcomes showed minimal operative mortality and low postoperative morbidity. Mortality was confined to early postoperative complications, with no intraoperative deaths. Perioperative issues like myocardial infarction, arrhythmias and pulmonary complications were less and managed effectively, with satisfactory ICU support and hospital stay durations. Conclusion: CABG surgery at CMCH is safe and effective, with results comparable to national and international standards. The success highlights the importance of skilled teams and comprehensive care, demonstrating CMCH’s ability to offer safe cardiac surgery despite early challenges. JCMCTA 2024 ; 35 (2) : 42-48